Status “Uang Panjaputan Sumando” Dalam Masyarakat Adat Minangkabau Ditinjau Dari Hukum Islam Di Nagari Salimpaung, Kecamatan Salimpaung, Kabupaten Tanah Datar - Khairat, Najmil; Elimartati, Elimartati (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
X This article examines the Sumando Panjaputan Money Tradition in the Minangkabau indigenous people in terms of Islamic law in Nagari Salimpaung, Salimpaung sub-district, Tanah Datar Regency. The purpose of this study is to explain the process of sumando panjaputan money in Nagari Salimpaung in the view of Islamic law. The type of research used is field research, namely in Nagari Salimpaung, Salimpaung District, Tanah Datar Regency. The author manages the data qualitatively with data sources that the author does by interviewing resource persons from Community Leaders, Alim Ulama, Niniak Mamak, chairman of KAN, the Wali Nagari salimpaung apparatus. The data obtained will be analyzed by descriptive analysis. The results of the author's research indicate that the process and status of Sumando's Panjaputan Money in Nagari Salimpaung is carried out by means of deliberation between male Niniak Mamak and female Niniak Mamak, the pick-up of Sumando is discussed on a predetermined day. The view of Islamic Law on the Status of Sumando's Panjaputan Money Tradition in Nagari Salimpaung that this Panjaputan Money tradition does not violate the provisions of syara', and Syara' also does not prohibit, reject and accept. This tradition falls into the status of Mubah, meaning that it can be carried out by the community as long as it fulfills the element of 'Urf Sahih, in the sense that it contains benefits and does not cause harm.